Metaphor as linguistic instrument of manipulation to realize the persuasive strategy in the texts of Spanish political parties programs - Irina Smirnova (Ибероамериканские тетради, 2017)
Text of any party program is communicative that is it contains information that an author transfers to a recipient. This information can serve as a source of knowledge about phenomena and events as well as to be a source of a strong emotional impact on recipient encouraging him to act certain way. Since the emotional sphere is one of the levers that controls behaviour of any person, it is very important for the authors of the pre-election political programs to make an impact on readers and also make an ideological settingdesired for these authors.To use kilfully the mechanism of persuasiveness is to get electoral support of the electorate. One of such mechanisms used in the texts of the pre-election polititical programs is using of metaphors. Page 79 И. В. Смирнова79The political metaphor is very sensitive to events happening in the country and language of politics. It is one of the most signi cant and common methods of language manipulation that capable of long conserving in memory and making an impact on the recipient’s associative thinking. The use of metaphors in political discourse is mostly applied for manipulation of the electorate and their use is also a powerful persuasion technique.